2015
DOI: 10.1074/jbc.m115.661553
|View full text |Cite
|
Sign up to set email alerts
|

The BAP1/ASXL2 Histone H2A Deubiquitinase Complex Regulates Cell Proliferation and Is Disrupted in Cancer

Abstract: Background:The relevance of ASXL2 to the function of the histone H2A deubiquitinase BAP1 remains unknown. Results: ASXL2 promotes the assembly by BAP1 of a composite ubiquitin-binding interface (CUBI) required for DUB activity and coordination of cell proliferation. Conclusion: Cancer-associated mutations of BAP1 disrupt BAP1-ASXL2 interaction and function. Significance: We provide novel insights into BAP1 tumor suppressor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 66 publications
8
121
0
Order By: Relevance
“…EZH2 is the catalytic component of Polycomb Repressive Complex 2 (PRC2) and serves as a H3K27 methyltransferase activity. ASXL1 and ASXL2 are part of the Polycomb repressive deubiquitinase complex, which removes an ubiquitin from H2AK119 marks, 42 but studies have shown that ASXL proteins may also function in recruitment and/or stabilization of the PRC2 complex to specific loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EZH2 is the catalytic component of Polycomb Repressive Complex 2 (PRC2) and serves as a H3K27 methyltransferase activity. ASXL1 and ASXL2 are part of the Polycomb repressive deubiquitinase complex, which removes an ubiquitin from H2AK119 marks, 42 but studies have shown that ASXL proteins may also function in recruitment and/or stabilization of the PRC2 complex to specific loci.…”
Section: Discussionmentioning
confidence: 99%
“…34 The 4 subunits form a ring structure that regulates chromosome segregation during meiosis and mitosis, but recent data suggest additional functions such as double-stranded DNA repair and regulation of transcription. 42,45 In a previous study by Thol et al, recurrent cohesin mutations have been reported in about 6% of AML patients. 45 However, cohesin mutations concerned less than 2% of CBF AML in this study.…”
mentioning
confidence: 92%
“…ASXL proteins also interact with BRCA-1 Associated Protein-1 (BAP1), a ubiquitin hydrolase that mediates de-ubiquitination of H2AK119Ub, the repressive mark placed by the “maintenance” PRC1 (43). BAP1 does not interact with PRC2 proteins (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although both ASXL1 and ASXL2 have been identified to bind to BAP1, recent biochemical characterization of BAP1 complexes by Daou et al (2015) suggest that BAP1 forms two mutually exclusive complexes with ASXL1 and ASXL2. In this study, BAP1 was identified to stabilize ASXL2 via deubiquitination of ASXL2.…”
Section: Effect Of Asxl Mutations On Asxl Functionmentioning
confidence: 99%